EVALUASI EFISIENSI PENGGUNAAN BETON BERTULANG PADA STRUKTUR JEMBATAN - Bagus Nugroho Prasetyo; Edison H Manurung (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Efficiency in bridge construction is a critical multidimensional concept, encompassing structural, economic, and time aspects. This study aims to evaluate the efficiency of reinforced concrete use in bridge structures through a comparative analysis of various design parameters. The method used is applied research with a quantitative approach, through parametric design simulations of 18 scenarios which are a combination of cross-section type variables (T-Beam and Box Girder), concrete quality (K-300, K-350, K-450), and span length (20m, 30m, 40m). The analysis was carried out in an integrated manner with SAP2000 software for structural modeling and manual calculations based on SNI 2847:2019 and RSNI T-02-2005 for reinforcement design and cost analysis.The study results show that box girders are consistently more structurally efficient, with up to a 22% reduction in concrete volume compared to T-beams over a 30m span, especially when using high-grade concrete (K-450). However, from an economic efficiency perspective, conventional T-beams remain superior, with initial construction costs 4.6% lower under similar conditions, driven by lower formwork and labor costs. A weighted multi-criteria analysis reveals that the most efficient option depends heavily on project priorities: conventional K-350 T-beams are optimal for cost-oriented projects, while precast K-450 box girders excel for projects prioritizing speed and performance. The study concludes that there is no universally best solution and recommends analyzing design alternatives at the concept stage to achieve holistic resource optimization in bridge planning in Indonesia